Effect of nano-emulsion coating of Dracocephalum Kotschyi essential oil in chitosan on quality of sprouted wheat using response surface methodology (RSM) - Nasim Najafi; Hajar Abbasi (مجله پژوهش‌های علوم و صنایع غذایی ایران, 2021)
Introduction highly sensitive to fungal and biochemical changes such as respiration and enzymatic activity, as a result, it has a short shelf life: wheat is an important cereal crop used as staple food in many parts of the world and provides 20% of the energy and 78-93% of the protein in the human diet. Seed germination is a process which begins with activating proteinase due to uptake of water. Metabolic activity occurs during the germination process, leading to the hydrolysis of proteins and carbohydrates, and the synthesis of metabolites that have health-promoting properties for human. Sprouted wheat is a rich source of protein, dietary fiber, minerals, vitamins and phytosterols. Using chemical preservatives to extend the shelf life of food has a great health concern for many years. Therefore, developing safe methods to control perishability and maintain quality of perishable foods during storage is crucial. Chitosan is a linear polysaccharide composed of randomly distributed β-(1-4)-D-glucosamine and N-acetyl-D-glucosamine. Chitosan coating is beneficial to maintaining the storage quality and prolonging the shelf life of postharvest fruits and vegetables. Dracocephalum kotschyi is one of the medicinal herbs with special constituents including caryophyllene, limonene, α-pinene, geranial, and flavonoids. The essential oil of this plant has significant biological activities, including antiviral, antibacterial and anti-corruption. Considering the successful application of chitosan and essential oils in edible coating formulae and its proven antifungal properties due to its nano-particles prompted us to initiate this study aiming at assessing the efficiency of an edible coating for maintaining quality and increasing the shelf life of wheat sprout. Therefore, in the present study, nano-emulsion of Dracocephalum Kotschyi essential oil in chitosan was considered for coating sprouted wheat in order to delay its perishability. Materials and Methods: Materials used in this study consisted of wheat (Pakanbazr Co.), chitosan (Shayan Chemical Co.) and Dracocephalum kotschyi were supplied from Isfahan's medicinal plants market. All chemicals were from Merck Co. In order to prepare wheat germ, wheat grains were immersed in water containing 0.07 % sodium hypochlorite for 10 min. Then, the disinfected samples were soaked in water at 25 °C for 12 h. After soaking, the samples were placed in a germination chamber at 30 °C and 98% relative humidity for 48 h. Quality properties of sprouted wheat such as moisture, ash, fat, protein, mineral, fiber and ascorbic acid concentration were measured. Sprouted wheat was coated by immersion in nano-emulsion and then was packed at modified atmosphere (30% oxygen, 70% nitrogen), for 12 days at 4° C. The pH, weight loss, total phenol content, antioxidant activity and hardness of the samples were determined. Optimal and control samples were examined in terms of qualitative characteristics such as pH, weight loss, total phenol content, antioxidant activity and hardness during 0, 4, 8, 12, 16 and 20 days after production. In the present study, effects of independent variables such as essential oil concentration (A), chitosan concentration (B) and immersion time (C) on total phenolic content, antioxidant activity, ascorbic acid content, and hardness were investigated by Response Surface Method in the form of a central composite design with 6 central point (α=1.5). Comparison of the optimal and control samples was done in a completely randomized design using SAS ver: 9.1 software. Results and Discussion: An increase in chitosan and immersion time resulted in better preservation of total phenolic. The interaction effect of essential oil concentration and immersion time also resulted in better retention of total phenolic compounds. An increase in essential oil and chitosan concentration up to intermediate level increased the antioxidant activity. Chitosan and Dracocephalum Kotschyi essential oil play a  key role in maintaining the total phenolic content and antioxidant capacity of sprouted wheat by reducing gas exchange, respiration rate and the activity of polyphenol oxidase and peroxidase enzymes. Interaction effects of variables up to intermediate level resulted in higher level of preservation of ascorbic acid. The interaction effect of essential oil and chitosan at high levels led to better preserved of hardness. Coating treatment contains 25% chitosan with 84.18 ppm Dracocephalum Kotschyi essential oil and 25s immersion time can be introduced as a safe and effective method to maintain the quality characteristics and increase wheat sprout shelf life. Coating of wheat sprout reduced the changes in pH, weight loss, total phenol content, ascorbic acid, antioxidant activity and hardness in coated samples during storage compared to the control sample. Furthermore, sensory properties did not change significantly after storage time. The results revealed that the use of chitosan- Dracocephalum Kotschyi oil coating delay bacterial and fungal decay and improved the quality characteristics and shelf life of sprouted wheat during storage. The results of this study indicated the positive effect of chitosan-Dracocephalum Kotschyi oil nano-emulsion coating on preserving the quality of sprouted wheat